Functional asymmetries in the movement kinematics of patients with Tourette's syndrome. Issue 2 (1st August 1997) - Georgiou, Nellie; Bradshaw, John L; Phillips, Jim G; Cunnington, Ross; Rogers, Mark
Abstract : OBJECTIVES: This study adopted a concurrent task design and aimed to quantify the efficiency and smoothness of voluntary movement in Tourette's syndrome via the use of a graphics tablet which permits analysis of movement profiles. In particular, the aim was to ascertain whether a concurrent task (digit span) would affect the kinematics of goal directed movements, and whether patients with Tourette's syndrome would exhibit abnormal functional asymmetries compared with their matched controls. Methods— Twelve patients with Tourette's syndrome and their matched controls performed 12 vertical zig zag movements, with both left and right hands (with and without the concurrent task), to large or small targets over long or short extents. Results —With short strokes, controls showed the predicted right hand superiority in movement time more strongly than patients with Tourette's syndrome, who instead showed greater hand symmetry with short strokes. The right hand of controls was less force efficient with long strokes and more force efficient with short strokes, whereas either hand of patients with Tourette's syndrome was equally force efficient, irrespective of stroke length, with an overall performance profile similar to but better than that of the controls' left hand. The concurrent task, however, increased the force efficiency of the right hand in patients with Tourette's syndrome and the left hand in controls. Conclusions— Patients with Tourette's syndrome, compared with controls, were not impaired in the performance of fast, goal directed movements such as aiming at targets; they performed in certain respects better than controls. The findings clearly add to the growing literature on anomalous lateralisation in Tourette's syndrome, which may be explained by the recently reported loss of normal basal ganglia asymmetries in that disorder.